Acceptability of the Transitional Wearable Companion “+me” in Children With Autism Spectrum Disorder: A Comparative Pilot Study - Sperati, Valerio; Özcan, Beste; Romano, Laura; Moretta, Tania; Scaffaro, Simone; Faedda, Noemi; Turturo, Giada; Fioriello, Francesca; Pelosi, Simone; Giovannone, Federica; Sogos, Carla; Guidetti, Vincenzo; et al. (Frontiers in Psychology, 2020)
+me is an experimental interactive soft toy, looking like a panda, developed for young children. When touched on paws or head (inputs), the toy can emit attractive responses such as coloured lights and amusing sounds (outputs). +me is wirelessly connected to a control tablet through which an adult caregiver can modify its input-output contingencies, so as to produce different, rewarding response patterns using the same device. Given these features, we propose +me as a potential novel tool to support the therapy of Autism Spectrum Disorder (ASD). The allure of the device could indeed be exploited to capture the attention and encourage the social interaction of toddlers during play activities with therapists. In this pilot study +me was tested on two small groups of children aged 30-48 months, one diagnosed with ASD and a second one with Communication Disorder, a condition which often presents –especially at early age– overlapping sympthoms with ASD. The proposed play activities aimed to foster simple imitative behaviours and stimulate the engagement of children. Results were compared with those of a previous test run on Typically Developed children. Preliminary observations, based on the analysis of video recordings, suggest that on average +me is able to encourage a positive engagement and that different groups tend to manifest some different behaviours.